Modifikasi SLS dengan epoksida dari asam oleat dan hidrogen peroksida untuk meningkatkan kualitas surfaktan pada EOR - Chitra Ria Ariska; Suryo Purwono; Bardi Murachman (Jurnal Teknik Kimia Indonesia, 2011)
SLS modification using epoxyde from oleat acid and hydrogen peroxyde to improve the quality of surfactant in EORSurfactant is one of the compounds used in Enhanced Oil Recovery (EOR) which function is to enhance the oil production. One of the surfactants widely used is Sodium Ligno Sulfonat (SLS) due to its high degradability. However the modification with another compound is still needed in orderto decrease its Inter Facial Tension (IFT) until reach the ultralow IFT(±10-3 mN/m). One of the chemical compounds used to modify the surfactant is epoxidebecause it has reactive oxirane ring. The addition of oleic epoxide will increase solubility of surfactant in oil so it brings more stable microemulsion. Epoxidation of oleic acid was carried out with peroxyacetic acid that was generated insitu from aqueous hydrogen peroxide and glacial acetic acid. The modification of SLS was then done by adding the epoxide in various conversion resulted from epoxidation. The experiment was investigated at temperature, ratio of epoxide to SLS and reaction time of 70oC, 1:2 and 1 hour, respectively. The modified product were then measured their IFTat temperature of 30-60oC and tested the stability of microemulsion based on time of formation of microemulsion up back in its original state. The present study revealed that epoxides has capability to decrease IFT. The results of experiment shows that the lowest IFT is modification of epoxide with the conversion of 10% as 3,7 x10-3 mN/m and has most excellent stability with time 113 minutes.Keywords: epoxide, Sodium Ligno Sulfonat (SLS), microemulsion, surfactant, EOR AbstrakSurfaktan adalah salah satu bahan kimia yang digunakan dalam Enhanced Oil Recovery (EOR) untuk meningkatkan produksi minyak. Salah satu jenis surfaktan yang banyak digunakan adalah Sodium Ligno Sulfonat (SLS) karena mudah didegradasi limbahnya. Namun modifikasi dengan senyawa lain masih perlu dilakukan untuk menurunkan tegangan antarmuka atau Inter Facial Tension (IFT) hingga mencapai ultralow IFT (±10-3 mN/m). Salah satu bahan kimia yang dapat digunakan untuk modifikasi surfaktan adalah epoksida karena memiliki cincin oksiren yang reaktif. Penambahan epoksi oleat ini akan meningkatkan kelarutan surfaktan dalam minyak sehingga didapatkan mikroemulsi yang lebih stabil. Modifikasi SLS dibuat dengan menambahkan epoksida dengan variasi konversi yang dihasilkan dari proses epoksidasi. Percobaan dilakukan pada temperatur 70oC, rasio perbandingan epoksida:SLS adalah 1:2 dengan waktu reaksi 1 jam. IFT produk modifikasi diukur pada temperatur 30-60oC dan diuji kestabilan mikroemulsinya berdasarkan waktu pembentukan mikroemulsi sampai kembali pada keadaan semula. Dari penelitian didapatkan bahwa epoksida dapat menurunkan IFT. IFT paling rendah dihasilkan dari modifikasi epoksida dengan konversi 10%, yaitu 3,7 x10-3 mN/m dan memiliki kestabilan paling baik dengan waktu emulsi 113 menit.Kata kunci: epoksida, Sodium Ligno Sulfonat (SLS), mikroemulsi, surfaktan, EOR